Analysis of the Cash Flow Statement as a Tool for Strategic Decision-Making: A Case Study of PT Telkom Indonesia for the 2022–2024 Period - Nur Muhamad Hamka; Shira Raigung Renata; Qisty Saufa Abadi; Tri Ceysha Nur Wahyuni; Asri Sundari (Advances in Managerial Auditing Research, 2026)
Purpose: This study aims to analyze the cash flow trends of PT Telkom Indonesia (Persero) Tbk from 2022 to 2024 and assess their relationship to strategic decisions based on the company’s documentary evidence. Research Method: The research employed a descriptive case study using a mixed-methods approach based on document analysis. Analysis of changes and cash flow ratios was integrated with content analysis of financial statements, annual reports, sustainability reports, and the company’s official disclosures. Results and Discussion: Operating cash flow remained positive, but in 2023–2024 it had not yet returned to 2022 levels. In 2024, a decline in fixed asset purchases boosted free cash flow, dividend payments increased, and the composition of debt receipts and payments changed. These findings indicate changes in cash capacity and allocation, but do not prove that the cash flow statement directly determines investment, financing, or dividend decisions. Implications: Cash flow analysis must be combined with information on earnings, financial position, financial statement notes, and management’s discussion and analysis to evaluate the company’s decisions properly. Originality: This study integrates numerical analysis and documentary evidence and distinguishes financial indicators from direct evidence of decision-making.